Hereditary neuralgic amyotrophy in childhood caused by duplication within the SEPT9 gene: A family study. Issue 1 (10th October 2018) - Neubauer, Katharina; Boeckelmann, Doris; Koehler, Udo; Kracht, Julia; Kirschner, Janbernd; Pendziwiat, Manuela; Zieger, Barbara
Abstract: Hereditary neuralgic amyotrophy (HNA) is an autosomal dominant disorder associated with episodic, recurrent, and painful neuropathies affecting the nerves of the brachial plexus. In this study, we report on a family of Lebanese descent with HNA onset in early childhood. The affected family members presented with platelet dysfunction. Platelet aggregation was reduced after stimulation with the agonists ADP and epinephrine in all affected family members. Flow cytometric analyses revealed impaired platelet δ‐secretion. The index patient and one brother suffered from kidney cysts. Molecular genetic analysis revealed a heterozygous duplication of exon 2 within the septin 9 ( SEPT9) gene in all the affected family members. Such a young child with HNA (aged 2 years) caused by SEPT9 duplication has not been described so far.